Multibeam bathymetry raw data (EM 120 echosounder entire dataset) of RV MARIA S. MERIAN during cruise MSM15/3 - Katrin Huhn; Christian dos Santos Ferreira (PANGAEA, 2022)
Multibeam bathymetry raw data using the ship extquotesingles own Kongsberg (Simrad) EM 120 multibeam echosounder was not continuously recorded during RV MARIA S. MERIAN cruise MSM15/3. Data was recorded on 2 days between 2010-06-25 and 2010-06-27. This dataset contains a survey south of Sicily and an elongated extend of this survey to the east. The approximate average depth of the entire dataset is around 3200m. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. No ancillary sound velocity profiles (SVP) files from the cruise are archived at the BSH, thus no SVP files are added to this dataset. However, also data analysis of the multibeam raw data revealed that SVP has been changed once during the survey. This publication is conducted within the efforts of the German Marine Research Alliance in the core area "Data management and Digitalization" (Deutsche Allianz Meeresforschung, DAM). Data are unprocessed and therefore contains incorrect depth measurements (artifacts) without further processing. Note that refraction errors can be expected due to the lack of proper SVP. Overall, it appears that the data quality is rather good since the gridded hillshade data showed relatively few obstacles. Nevertheless, it seems that data has been cut off in some areas. Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).